Terra-i+ webtool: Simplifying agroforestry sustainability monitoring - Nguyen, Phuong Minh; Luong, Phuong Thi; Vantalon, Thibaud; Reymondin, Louis; Talsma, Tiffany; Phan, Trong Van; Nguyen Thi, Thuy Thu; Bunn, Christian (2023)
In an ever-evolving landscape of regulations and commitments to net-zero emission commodity chains, Terra-i+ offers a satellite-based solution for agroforestry supply chain sustainability management. At its core, Terra-i+ functions as an integrated platform to access critical information about the sustainability status of coffee supply chains. With Terra-i+, stakeholders gain access to essential metrics and insights, empowering them to make informed decisions that drive adoption of sustainable practices.